Higher Adherence to the Mediterranean Dietary Pattern Is Inversely Associated With Severity of COVID-19 and Related Symptoms: A Cross-Sectional Study - Zargarzadeh, Nikan; Tadbir Vajargah, Kiana; Ebrahimzadeh, Armin; Mousavi, Seyed Mohammad; Khodaveisi, Hamidreza; Akhgarjand, Camellia; Toyos, Fernando M. P.; Cerqueira, Henrique S.; Santos, Heitor O.; Taghizadeh, Mohsen; Milajerdi, Alireza (Frontiers in Medicine, 2022)
Background & Aims: Adherence to the Mediterranean diet (MD) has been associated with a decreased risk of developing a variety of chronic diseases that are comorbidities in COVID-19 patients. However, its association to the severity and symptoms of COVID-19 are still unknown. This study aimed to examine the association between adherence to the MD pattern and COVID-19 severity and symptoms in Iranian hospitalized patients. Methods: In this cross-sectional study, 250 COVID-19 patients aged 18 to 65 were examined. We employed a food frequency questionnaire (FFQ) to obtain data on dietary intake of participants in the year prior to their COVID-19 diagnosis. COVID-19 severity was determined using the National Institutes of Health's Coronavirus Disease 2019 report. Additionally, symptoms associated with COVID-19, inflammatory markers, and other variables were evaluated. The scoring method proposed by Trichopoulou et al. was used to assess adherence to the MD. Results: The participants' mean age was 44.1±12.1 years, and 46% of them had severe COVID-19. Patients who adhered more closely to the MD had lower serum C-reactive protein levels (7.80 vs. 37.36 mg/l) and erythrocyte sedimentation rate (14.08 vs. 42.65 mm/hr). Those with the highest Mediterranean diet score were 77% less likely to have severe COVID-19 after controlling for confounding variables. The MD score was also found to be inversely associated with COVID-19 symptoms, including dyspnea, cough, fever, chills, weakness, myalgia, nausea and vomiting, and sore throat. Conclusion: Higher adherence to the MD was associated with a decreased likelihood of COVID-19 severity and symptoms, as well as a shorter duration of hospitalization and convalescence, and inflammatory biomarkers.